Sociedade Libertadora Sete de Setembro and the national question. (TEL Tempo, Espaço e Linguagem, 2021)
Sociedade Libertadora Sete de Setembro was the most important emancipacionist society in the seventies from the Province of Bahia. From de analysis of a set of journals and documents produced by baiana’s association, this article discusses the project of emancipation proposed  and analizes its detachment in the face of civic celebrations´s most important of Province of Bahia at the time,  July 2th.